The Harmonization of Customary, State, and Islam in the Practice of Dayak-Muslim Senganan Customary Inheritance in Sintang, Indonesia - Fadani, Fadhil; Adib, Muhammad Adib Alfarisi (UIN Sunan Kalijaga Yogyakarta, 2024)
The powerful Dayak-Muslim Senganan customs often interact with Islamic teachings, particularly in matters such as inheritance, as regulated by the principles of faraid. This interaction presents challenges, especially when Islamic rules need to be adapted to long-standing customary norms. Additionally, the state plays a significant role in its national legal system, acting as a mediator or law enforcer to ensure that inheritance practices align with national laws. While the issue of customary law, Islam, and the state is frequently examined from a conflict perspective, this does not apply to Dayak-Muslim customary inheritance practices in Sintang Regency, West Kalimantan Province. This article examines the interaction of these three legal systems in inheritance practices, focusing on the Dayak-Muslims of Senganan. Using Andrea J. Hoekma's socio-legal approach, which emphasizes the integration of non-conflicting laws, this study conducted in-depth interviews with customary and formal authorities. The findings reveal that customary law, state law, and Islamic law coexist harmoniously, supporting the community's interests without conflict. Furthermore, the research shows that Dayak-Muslim inheritance practices do not contradict Islamic law. These seemingly distinct legal systems can be synthesized to form an effective inheritance system within specific social and cultural contexts. This research contributes to a broader understanding of the harmonization among customary law, Islam, and the state, demonstrating a dynamic of mutual influence and understanding. Adat Dayak-Muslim Senganan yang kuat sering kali bersentuhan dengan ajaran Islam, salah satunya mengenai kewarisan seperti yang diatur dalam faraid. Interaksi ini menimbulkan tantangan ketika aturan Islam harus disesuaikan dengan norma adat yang telah lama ada. Selain itu, negara berperan penting melalui sistem hukum nasionalnya sebagai mediator atau penegak hukum, memastikan bahwa praktik kewarisan mengikuti undang-undang nasional. Persoalan hukum adat, Islam dan negara sering kali dikaji melalui kacamata konflik, namun perspektif ini tidak berlaku bagi praktik pewarisan adat Dayak-Muslim di Kabupaten Sintang, Provinsi Kalimantan Barat. Artikel ini mengkaji ketiga sistem hukum dalam praktik kewarisan, khususnya di kalangan Dayak-Muslim Senganan. Artikel ini menggunakan pendekatan sosio-legal Andrea J. Hoekma, yang mengintegrasikan hukum yang tidak bertentangan. Melalui wawancara mendalam dengan para pemimpin adat dan formal, penelitian ini menemukan bahwa hukum adat, hukum negara, dan hukum Islam dapat hidup berdampingan secara harmonis, melayani kepentingan masyarakat tanpa pertentangan. Temuan penelitian juga mengungkapkan bahwa praktik pewarisan Dayak-Muslim tidak bertentangan dengan hukum Islam. Entitas yang tampaknya saling bertentangan, namun sebenarnya dapat bersinergi untuk menciptakan sistem kewarisan yang efektif dalam konteks sosial dan kultural yang spesifik. Penelitian ini berkontribusi pada pemahaman harmonisasi antara hukum adat, Islam, dan negara yang saling memengaruhi dan memahami satu sama lain.